Toward the realistions of the right of access to justice: a comparative analysis of the legal aid schemes in Tanzania and Ghana - Appiagyei-Atua, Kwadwo (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2008.